The Meaning Of Being A Family Reflected In Louisa May Alcott's Little Women (1868): Sociological Approach - Wulandari, Asri, Dr. M. Thoyibi, M.S, Siti Fatimah, S. Pd, M. Hum (2014)
This research paper is Knowing that the problem is the most important part of research, the writer purposes the problem as "what is the meaning of being a family are reflected in Louisa May Alcott's Little Women. So they writer makes title "the meaning of being a family reflected in Louisa May Alcott's Little Women (1868): Sociological Approach. The writer use The objectives of the research are : (1) To analyze Louisa May Alcott's Little Women novel based on its structural elements (2) To analyze the meaning of being a family in Louisa May Alcott's Little Women based on sociological approach. This research applies descriptive qualitative method research. The object of this research is Louisa May Alcott's Little Women novel, and the writer is going to analyze it by using sociological approach. The outcome of the study reveals the relationship between the novel and the social reality in American Society especially at the second half of nineteenth century. In Little Women by Louisa May Alcott describes about the meaning and importance of being a family. The issues is clearly related with social condition of America at the second half of nineteenth century.